Distribution of ABO and Rh Blood Group Systems in the General Population of Dhaka, Bangladesh: Insight from a Single-Centre Analysis (East West Medical College Journal, 2026)
Objective: This study aimed to analyze the distribution of ABO and Rh blood groups among the general population of Dhaka city. The findings provide updated insights into local blood group patterns, which can help optimize transfusion services and blood bank management.Method: A retrospective cross-sectional study was conducted at NILMRC, Dhaka. Data were collected from the Laboratory Information System (LIS) of NILMRC. A total of 10,176 individuals were included in the study, regardless of age, sex, or health condition. ABO and Rh blood groups were determined using both automated systems and the manual slide agglutination method.Results: The most common blood group was B (33.48%), followed closely by group O (33.33%), group A (24.12%), and group AB (9.07%). Rh-D positive individuals comprised 96.33% of the total population. Males were predominant in all blood groups, and 58% of participants were within the 18–30 years age group.Conclusion: B-positive was the most prevalent blood group among the population studied. Understanding the distribution of blood groups is essential for improving donor recruitment strategies and ensuring adequate blood availability for transfusion needs in the future.EWMCJ Vol. 14, No. 2, July 2026: 152-156